Determinan Pernikahan Usia Dini pada Remaja - Eva Erna Juliawati; Astrid Novita; Rita Ayu Yolandia (SIMFISIS Jurnal Kebidanan Indonesia, 2021)
Introduction: According to the Marriage Law, Number 16 of 2019 article 7 paragraph (1) early marriage is a marriage that is carried out before a person reaches ≤19 years of age. Objectives: The purpose of this study is to determine the determinants of early marriage in adolescents. The determinants used in this study are economic factors, environmental factors, socio-cultural factors, mass media, as well as views and beliefs. Method: This study used a design cross-sectional, with a simple random sampling technique. And determining the sample using the Lemeshow formula to obtain a sample size of 50 respondents. Result: The results showed that 27 respondents (54%) were married aged 16-17 years, 30 respondents (60%) had low-income economic factors <UMK, 27 respondents (54%) had bad environmental factors, 29 respondents (58%) had social negative culture, 31 respondents (65%) were exposed to mass media, 28 respondents (56%) had negative views and beliefs. Conclusion: The results of the test Chi-Square showed that there was a significant relationship between early marriage among adolescents with economic factors p-value = 0.013 and OR = 5.444 (95% CI 1.584-18.714), environmental factors P-value = 0.026 and OR = 4.453 (95% CI 1.353 -14.653), socio-cultural P-Value = 0.027 and OR = 4.444 (95% CI 1.337-14.769), mass media P-Value = 0.028 and OR = 4.550 (95% CI 1.335-15,503), views and beliefs of P-Value = 0.002 and OR = 8,000 (95% CI 2.247- 28.477).